Groupthink in Political Participation in the 2019 presidential Election - Alifa Nur Fitri; M. Nuqlir Bariqlana; Adeni Adeni (IAIN Salatiga, 2021)
The 2019 Presidential election divided voters into two strongholds, namely the strongholds of Jokowi-Ma'ruf supporters and the stronghold of Prabowo-Sandi supporters. There has been an increase in political participation caused by the high cohesiveness of the group in supporting both candidates. The two sides attack each other even in some cases can damage family relationships and friendships due to differences in choice. The cohesiveness is evident from the swearing used to attack each group, Kampret is a swearing-in aimed at supporters of Prabowo- Sandi, and Cebong is a swearing-in aimed at supporters of Jokowi -Ma'ruf. The purpose of this paper is to see groupthink in political participants in the 2019 Presidential Election. The methodology used is descriptive qualitative. The results of this study show that groupthink occurred in the 2019 presidential election seen from several symptoms, namely each side shows the illusion of inconsistency, belief in ingrained morality, the existence of stereotypes of opposing groups, collective rationalization, self-censorship, pressure on opponents, mind guards and the illusion of unanimity.